Combining two outcome frames to promote support for obesity-related policies - Kim, Hye Kyung (2020)
Guided by construal level theory (CLT), this study investigates the interplay between two framing approaches that address outcomes of obesity-related policies. A randomized experiment (N = 299) was conducted with a 2 (gain- vs. loss-frame) X 2 (societal- vs. individual-frame) between-participants design. Consistent with CLT, frame combinations with consistent construal levels were more persuasive. Compared to a societal-loss frame, a societal-gain frame was perceived as a stronger argument, which in turn increased policy support. Participants were also more likely to engage in healthier diets and physical activity when messages highlighted societal-gain rather than societal-loss. This study offers important insights for combining multiple framing approaches in a persuasive message to improve policy support as well as individual health decisions.